Hypothalamic miR-103 protects from hyperphagic obesity in mice - Vinnikov, Ilya A.; Hajdukiewicz, Karolina; Reymann, Juergen; Beneke, Juergen; Czajkowski, Rafal; Roth, Lena C.; Novak, Martin; Roller, Andreas; Doerner, Nicole; Starkuviene, Vytaute; Theis, Fabian J.; Erfle, Holger; et al. (The Journal of Neuroscience, 2014)
The role of neuronal noncoding RNAs in energy control of the body is not fully understood. The arcuate nucleus (ARC) of the hypothalamus comprises neurons regulating food intake and body weight. Here we show that Dicer-dependent loss of microRNAs in these neurons of adult (DicerCKO) mice causes chronic overactivation of the signaling pathways involving phosphatidylinositol-3-kinase (PI3K), Akt, and mammalian target of rapamycin (mTOR) and an imbalance in the levels of neuropeptides, resulting in severe hyperphagic obesity. Similarly, the activation of PI3K-Akt-mTOR pathway due to Pten deletion in the adult forebrain leads to comparable weight increase. Conversely, the mTORC1 inhibitor rapamycin normalizes obesity in mice with an inactivated Dicer1 or Pten gene. Importantly, the continuous delivery of oligonucleotides mimicking microRNAs, which are predicted to target PI3K-Akt-mTOR pathway components, to the hypothalamus attenuates adiposity in DicerCKO mice. Furthermore, loss of miR-103 causes strong upregulation of the PI3K-Akt-mTOR pathway in vitro and its application into the ARC of the Dicer-deficient mice both reverses upregulation of Pik3cg, the mRNA encoding the catalytic subunit p110γ of the PI3K complex, and attenuates the hyperphagic obesity. Our data demonstrate in vivo the crucial role of neuronal microRNAs in the control of energy homeostasis. © 2014 the authors.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dicer; Hypothalamus; Metabolism; Mice; MicroRNA; Obesity